Application of Cad Systems to Accounting for Mechanical Stresses in the Development of Uncooled Thermal Detectors of the Bolometric Type - Tran Van Trieu; I. Yu. Lovshenko; V. R. Stempitsky; K. V. Korsak; Tran Tuan Trung; Dao Dinh Ha; V. V. Kolos (Цифровая трансформация)
A comparative analysis of the characteristics of the main types of bolometers is indicated in the article. The constructive solution of an uncooled thermal detector of the bolometric type, formed using the technology of microelectromechanical systems, is studied. By means of computer simulation in modern computer-aided design systems in microelectronics, a static mechanical analysis was performed to assess the effect of mechanical stresses arising in structural materials during their formation on the magnitude of deformation. It has been established that to ensure the normal functioning of the microbolometer (to reduce the maximum deviation value of the film from the nominal value), it is necessary to reduce the internal mechanical stresses in the NiCr film. For the Si3N4 films, on the contrary, this value should be increased.